A Prospective Study of the Clinical Content of Palliative Medicine Interdisciplinary Team Meetings. (December 2015) - Powazki, Ruth D.; Walsh, Declan; Shrotriya, Shiva
Structured interprofessional communication should improve the structure and clarity of the plan of care. The interdisciplinary team meeting (IDTM) is an opportunity for shared information on patients' and family care needs. We report a prospective observations study of palliative medicine IDTM, which recorded the clinical issues discussed. One hundred and forty-five disparate clinical items were identified for 59 patients and were discussed by the IDTM in about 240 minutes. By content analysis and research meeting consensus, they were grouped into 9 agreed interdisciplinary themes. The 9 themes were then subjected to biostatistical analysis and 3 communication clusters identified. Themes consisted of 3 major communication clusters: (1) clinical services, (2) psychosocial, and (3) care plan. Two themes (information exchange and clinical transitions) did not cluster. The IDTM identified patient care need, reported concerns, and supported collaboration in proactive patient care plans. Future research projects with more patients and a large number of meetings can confirm our findings. This should also examine specific contributions by professional discipline.